The relationship between age at menarche and infertility among Chinese rural women. (November 2015) - Chen, Jianping; Zhong, Chunli; Liang, Hong; Yang, Yuan; Zhang, Ou; Gao, Ersheng; Chen, Aimin; Yuan, Wei; Wang, Jian; Sun, Fei; Miao, Maohua
Abstract: Objective: To explore the relationship between age at menarche and infertility. Study design: The cross-sectional study investigated 6906 couples from the communities in Sandu Shui Autonomous County of Guizhou Province, China. Face to face interviews were conducted to collect information on age at menarche and time to first pregnancy, as well as demographic characteristics and lifestyle factors. Infertility was defined as being unable to become pregnant after attempting for ≥12 months. Poisson regression was used to assess the relationship between age at menarche and infertility of first attempt. Results: The prevalence rate of infertility for the first pregnancy attempt of the study population was 11.87%. There is an obvious monotonic, almost linear, trend of prevalence rate of infertility with increasing age at menarche ( P for trend: <0.001). Compared with wives with age at menarche of 13 years, the prevalence ratios of infertility were 0.71 (95%CI: 0.42, 1.20), 1.33 (95%CI: 1.05, 1.68), 1.47 (95%CI: 1.17, 1.85), 1.57 (95%CI: 1.20, 2.04), 1.41 (95%CI: 1.00, 1.99) and 1.73 (95%CI: 1.18, 2.52) for wives with age at menarche of ≤12, 14, 15, 16, 17 and ≥18 years, respectively, after adjusting for wife's year at birth, age at marriage, ethnic group, education and occupation, and husband's smoking and drinking habits before marriage. Conclusions: The present community-based study indicated that increasing age at menarche was associated with an increased risk of infertility in the study population.